Apnoea and brain swelling in non-accidental head injury. Issue 6 (1st June 2003) - Kemp, A M; Stoodley, N; Cobley, C; Coles, L; Kemp, K W
Abstract : Aims: (1) To identify whether infants and young children admitted to hospital with subdural haematomas (SDH) secondary to non-accidental head injury (NAHI), suffer from apnoea leading to radiological evidence of hypoxic ischaemic brain damage, and whether this is related to a poor prognosis; and (2) to determine what degree of trauma is associated with NAHI. Methods: Retrospective case series (1992–98) with case control analysis of 65 children under 2 years old, with an SDH secondary to NAHI. Outcome measures were presenting symptoms, associated injuries and apnoea at presentation, brain swelling or hypoxic ischaemic changes on neuroimaging, and clinical outcome (KOSCHI). Results: Twenty two children had a history of apnoea at presentation to hospital. Apnoea was significantly associated with hypoxic ischaemic brain damage. Severe symptoms at presentation, apnoea, and diffuse brain swelling/hypoxic ischaemic damage were significantly associated with a poor prognosis. Eighty five per cent of cases had associated injuries consistent with a diagnosis of non-accidental injury. Conclusions: Coma at presentation, apnoea, and diffuse brain swelling or hypoxic ischaemia all predict a poor outcome in an infant who has suffered from SDH after NAHI. There is evidence of associated violence in the majority of infants with NAHI. At this point in time we do not know the minimum forces necessary to cause NAHI. It is clear however that it is never acceptable to shake a baby.